PERANCANGAN SISTEM INFORMASI PINJAMAN DAN ANGSURAN DI KOPERASI KARYAWAN PT. INSANSANDANG INTERNUSA RANCAEKEK - Dheanita Senjaya Putri; Encep Supriatna (Ma'soem University, 2018)
Based on the research done, the authors found problems in the service activities loans and installmentas that are still not yet computerized well, to increase the service these activitiesthen required a program that can handle it.Before design programs to be used to support services in the cooperative an employee of PT. Insansandang Internusa Rancaekek, writer do research by a method of descriptive using a technique data collection in observation, interview, study documentation and the literature study.Methods used to analyzes and design systems information loans and installments this is the method System Development Life Sycle (SDLC) with the model Waterfall. To analyze systems needs the use writers instrument modeling data Flowmap, Data Flow Diagram (DFD), Entity Relationship Diagram, Structure Chart dan The Lexicographer Data. While for application program the writer use software Microsoft Visual Foxpro 9.0.This system designed writer expected to assist in service and management loans and installment data, so transactions and reports necessary produces more effective and efficient.